Inhibition of metastatic brain cancer in Sonic Hedgehog medulloblastoma using caged nitric oxide albumin nanoparticles - Soltys, Bohdan J.; Grausam, Katie B.; Messerli, Shanta M.; Hsia, Carleton J. C.; Zhao, Haotian (Frontiers in Oncology, 2023)
Medulloblastoma is a tumor of the cerebellum that metastasizes to the leptomeninges of the central nervous system (CNS), including to forebrain and to spinal cord. The inhibitory effect of polynitroxylated albumin (PNA), a caged nitroxide nanoparticle, on leptomeningeal dissemination and spinal cord metastatic tumor growth was studied in a Sonic Hedgehog (SHH) transgenic mouse model. PNA treated mice showed an increased lifespan with a mean survival of 95 days (n = 6, P<0.05) compared with 71 days in controls. In primary tumors, proliferation was significantly reduced and differentiation was significantly increased (P<0.001) as shown by Ki-67+ and NeuN+ immunocytochemistry, while cells in spinal cord tumors appeared unaffected. Yet, histochemical analysis of metastatic tumor in spinal cord showed that the mean total number of cells in spinal cord was significantly reduced in mice treated with PNA compared to albumin vehicle (two-tailed unpaired test, P<0.05). Examination of various level of the spinal cord showed that PNA treated mice had significantly reduced metastatic cell density in the thoracic, lumbar and sacral spinal cord levels (two-tailed unpaired test, P<0.05), while cell density in the cervical region was not significantly changed. The mechanism by which PNA may exert these effects on CNS tumors is discussed.